The Effectiveness of E-Learning Platforms in Enhancing Teacher Competencies in Vocational Education in makassar - Syarif (Mauve Journal De Leardu, 2025)
This study investigates the effectiveness of e-learning platforms in improving the competencies of vocational school teachers in Makassar. Using a mixed-methods design, it combined quantitative and qualitative approaches with fifty teacher participants. The study measured pedagogical, professional, technological, assessment, and communication competencies before and after the use of e-learning. Quantitative results indicated significant improvements in all areas, particularly in technological competence. Qualitative findings revealed that teachers benefited from using e-learning by adopting innovative teaching methods, providing timely feedback, and improving communication with students and colleagues. They also enhanced collaboration and professional growth through peer interaction on the platforms. Although initial obstacles such as limited internet access and lack of digital familiarity existed, teachers adapted successfully through training and continuous practice. The findings confirm that e-learning not only strengthens technical skills but also enhances pedagogical practices and professional development. This study concludes that digital learning environments are essential for advancing teacher competence and improving vocational education quality while emphasizing the need for sustained training and institutional support.